Analysis performance of Waja car air-conditioning system - Muhamad Amirudin, Kamalrul Badri (2009)
Air-conditioning system is important in nowadays life style due to it is capable to maintain the level of life in comfort level. Due to its functions, which are to maintain the temperature in the room, also to control the cleanness in room, air-conditioner is among the popular device that been use around the world. It’s having been use widely in houses, office rooms, supermarkets and cars. This thesis represents the analysis of air-conditioning system in Waja car, which is common car use by Malaysian. The objective of this thesis is to analysis the relationship of performance of air-conditioning system and speed of compressor with period of time. The thesis describes the fundamental of air-conditioning system, the way the system works and briefly explanation of each component involved in air-conditioning system. The experiment procedures are explained to obtain the important parameters and data. Finally, manual calculation is used to calculate the coefficient of performance of the system. The acquired results indicate the performance is decrease due to higher speed of compressor and the longer the system running. The obtained results show the performance decrease slightly in low speed of compressor compared than in high sped of compressor. The results concluded that the system at the unsteady state in low speed of compressor and it is become steady state at high speed of compressor. However the experiment is done with no velocity of winds outside the system. The results maybe change if the car is moving in high speed because the winds can help in heat transfer in condenser. The results can significantly reduce the cost of fuel when the car in standstill state.